Patient and family preferences about place of end-of-life care and death - Pinto, Sara (2024)
Funding Information: All authors have completed the Unified Competing Interest form (available on request from the corresponding author) at www.icmje.org/disclosure-of-interest/. BG is first author of one included systematic review. She did not take part in the selection, quality assessment, data extraction, analysis or conclusions in relation to this study. The authors thank Edoardo Aromataris (Director of Synthesis Science at the JBI, University of Adelaide), Kawaldip Sehmi (Chief Executive Officer of IAPO), Stecy Yghemonos (Director of Eurocarers), Isabel Andrade (Head Librarian at Nova National School of Public Health, Universidade Nova de Lisboa) and Barbara Antunes (Visiting Researcher at the University of Cambridge) for their contribution to the protocol and review development. This work is part of the project ´EOLinPLACE: Choice of where we die: a classification reform to discern diversity in individual end of life pathways´, which has received funding from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (grant agreement No 948609). The funder had no role in the protocol development and in the review execution, analysis, interpretation of the data, or decision to submit results. BG (the guarantor of the review) declares that the manuscript is an honest, accurate, and transparent account of the study being reported; no important aspects of the study have been omitted and any discrepancies from the study as planned (and, if relevant, registered) have been explained. Funding Information: All authors have completed the Unified Competing Interest form (available on request from the corresponding author) at www.icmje.org/disclosure-of-interest/. BG is first author of one included systematic review. She did not take part in the selection, quality assessment, data extraction, analysis or conclusions in relation to this study. The authors thank Edoardo Aromataris (Director of Synthesis Science at the JBI, University of Adelaide), Kawaldip Sehmi (Chief Executive Officer of IAPO), Stecy Yghemonos (Director of Eurocarers), Isabel Andrade (Head Librarian at Nova National School of Public Health, Universidade Nova de Lisboa) and Barbara Antunes (Visiting Researcher at the University of Cambridge) for their contribution to the protocol and review development. This work is part of the project ´EOLinPLACE: Choice of where we die: a classification reform to discern diversity in individual end of life pathways´, which has received funding from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (grant agreement No 948609). The funder had no role in the protocol development and in the review execution, analysis, interpretation of the data, or decision to submit results. BG (the guarantor of the review) declares that the manuscript is an honest, accurate, and transparent account of the study being reported; no important aspects of the study have been omitted and any discrepancies from the study as planned (and, if relevant, registered) have been explained. Publisher Copyright: © 2024 The Authors